2018
DOI: 10.1039/c8mt00193f
|View full text |Cite
|
Sign up to set email alerts
|

A histidine-richPseudomonasmetallothionein with a disordered tail displays higher binding capacity for cadmium than zinc

Abstract: Metallothioneins (MTs) are crucial players in metal-related physiological processes. They are characterized by a high cysteine content and unique metal binding properties resulting in specific metal-thiolate clusters formation. Here we present the first NMR solution structure of a Pseudomonas MT, PflQ2 MT, using the strain P. fluorescens Q2-87. It consists of a metal binding domain and an intrinsically disordered C-terminal tail, that was not observed in other MTs so far. While not influencing the structure or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…1). 7 Our studies revealed that the long C-terminal tail is intrinsically disordered and neither influencing the metalbinding properties nor the structure of the rest of the protein. However, it might potentially serve as a biologically relevant binding site for globular proteins or other interacting molecules.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…1). 7 Our studies revealed that the long C-terminal tail is intrinsically disordered and neither influencing the metalbinding properties nor the structure of the rest of the protein. However, it might potentially serve as a biologically relevant binding site for globular proteins or other interacting molecules.…”
Section: Introductionmentioning
confidence: 72%
“…The shortened version of the protein lacking the C-terminal tail, sh_PpKT MT (residues 1-51) was constructed in the same manner. Both newly constructed plasmids, as well as previously constructed plasmids of the fulllength PflQ2 MT and its shortened version sh_PflQ2 MT, 7 were used as a DNA template for the site-directed mutagenesis to construct the C28S and S29C mutants, respectively. Oligonucleotides used for the site-directed mutagenesis are listed in Table S1 (ESI †).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 3 more Smart Citations